The Role of Federal and Private Student Loans in Homeownership Decisions. Issue 1 (22nd April 2019) - Robb, Cliff A.; Schreiber, Samantha L.; Heckman, Stuart J.
Abstract : This paper examines the effect of student loans on the decision to become a homeowner. Analyses use the Baccalaureate and Beyond 2008:2012 (B&B) panel dataset collected by the U.S. Department of Education that surveyed a representative sample of four‐year college graduates from institutions across the country. Whereas previous analyses of student loan debt rely on cumulative loan balances, the present research examines both federal and private student loan impacts separately. Private student loan data is often unavailable in major datasets, but the B&B data provide rich information on sources and amounts of debt for recent graduates. We instrument student loans using in‐state tuition rates and find that for four‐year college graduates, a $1, 000 increase in a respondent's private student loan balance lowers the likelihood of buying a home by about 5 percentage points whereas a $1, 000 increase in federal loans has no significant impact on homeownership during this time.